Challenges in the use of extracorporal livers technologies - Karmouche, Andrea; Siroma, Thais; Siqueira, Giselle; Assis, Tayla (International Journal for Innovation Education and Research, 2022)
The human liver is a necessary organ in metabolism but when its working is harmed, can cause liver failure in varying degrees and raise the mortality rate. The only existing treatment for the disease so far is liver transplantation. Therefore, the objective of this research was to a evaluate the challenges of the artificial technologies of liver support (ATL) developed in the last nine years existing in the world. The technologies evaluated were those that consider the patient's need have a survival while waiting of the transplant or confirm that will not need the donated liver. This research is of type descriptive and bibliographical and was based on scientific articles published in the following databases: National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO), Academic Google, Latin American and Caribean Literature in Health Sciences (LACLHS), Virtual Health Library (VHL) and Capes Journal (Brazil). In the studies found, was verified that extracorporeal liver support technologies of the bioartificial type and artificial liver do not guarantee sufficient patient survival. Although this technologies have some clinical benefit with their use, is possible that the recipient patients suffer from metabolic intoxication. So that technologies can produce survival expected in patients, should be considered three pillars: the disease, the technology used and the dose of therapy. This research is important because it will help in the development of new methodologies better suited to recipientes.